2014
DOI: 10.4103/0259-1162.134506
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ropivacaine and ropivacaine with dexamethasone in supraclavicular brachial plexus block for postoperative analgesia

Abstract: Background:Mixing of various adjuvants has been tried with local anesthetics in an attempt to prolong anesthesia from peripheral nerve blocks but have met with inconclusive success. More recent studies indicate that 8 mg dexamethasone added to perineural local anesthetic injections augment the duration of peripheral nerve block analgesia.Aims:Evaluating the hypothesis that adding dexamethasone to ropivacaine significantly prolongs the duration of analgesia in supraclavicular brachial plexus block compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Akin to our study, a comparative study conducted by Kumar et al ., using 0.5% ropivacaine with or without 8 mg dexamethasone, reported better (85%) surgeon satisfaction score in dexamethasone group as compared to control group (62.5%). [ 20 ] In our study, perioperative heart rate and blood pressure recordings in patients receiving dexmedetomidine for block were on lower side, but this was statistically insignificant. No patient developed significant bradycardia.…”
Section: Discussionmentioning
confidence: 50%
“…Akin to our study, a comparative study conducted by Kumar et al ., using 0.5% ropivacaine with or without 8 mg dexamethasone, reported better (85%) surgeon satisfaction score in dexamethasone group as compared to control group (62.5%). [ 20 ] In our study, perioperative heart rate and blood pressure recordings in patients receiving dexmedetomidine for block were on lower side, but this was statistically insignificant. No patient developed significant bradycardia.…”
Section: Discussionmentioning
confidence: 50%
“…[ 15 ] In a study comparing dexamethasone at different doses as an adjuvant to bupivacaine for SCBP block, it was observed that 1 mg and 2 mg of dexamethasone prolonged the sensory and motor block duration to same extent as 4 mg.[ 16 ] Addition of dexamethasone (8 mg) to 30 mL of ropivacaine (0.5%) in brachial plexus block prolonged motor and sensory blockade as compared to ropivacaine alone, but it had no effect on the onset of sensory and motor block. [ 17 ] A meta-analysis concluded that dexamethasone produced late onset of sensory and motor block with prolongation of motor block duration and that the smaller doses of dexamethasone (4-5mg) were as equally effective as higher doses of dexamethasone (8-10mg). [ 18 ] However, the meta-analysis did not analyse any study using dexamethasone (8 mg) with levobupivacaine in supraclavicular brachial plexus block.…”
Section: Discussionmentioning
confidence: 99%
“…As far as time to first rescue analgesia was concerned, our study is in complete agreement with above studies. [ 15 16 17 18 ] but no agreement was found regarding the onset of block. In another study, the addition of 8 mg of dexamethasone to 30 mL of levobupivacaine reduced the onset of sensory and motor block and provided prolonged analgesia in supraclavicular brachial plexus block by paraesthesia technique.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria included pregnancy, diabetes mellitus, coagulopathy, local skin infection, surgeries with duration more than 180 min, and patients with allergy to local anesthetics or dexamethasone. The sample size was calculated based on a study by Kumar et al using ropivacaine and dexamethasone,[6] in which the mean duration of analgesia was 1179 ± 108.6 min. Considering this and to detect an effect size of 100 min with power of 80% and α error of 5%, the sample size calculated is 18.28 per group and we included 25 patients per group.…”
Section: Methodsmentioning
confidence: 99%